Ultralong-range energy transfer by interatomic Coulombic decay in an extreme quantum system - Sisourat, Nicolas; Kryzhevoi, Nikolai V.; Kolorenč, Přemysl; Scheit, Simona; Jahnke, Till; Cederbaum, Lorenz S. (Nature physics, 2010)
Interatomic Coulombic decay is a recently discovered ionization process by which energy absorbed from incident radiation by one atom is rapidly transferred to another. A study of this process in helium now shows that it can operate over remarkably long distances of more than 45 atomic radii.
Gesehen am 09.08.2023